Найдем значение выражения (16 * x) ^ (3/4) × (1/8 * x^ (3/8)) ^ (- 2/3). Для решения используем свойства степеней: (a ^ n) ^ m = a ^ (n * m), a ^ n * a ^ m = a ^ (n + m), a ^ n / a ^ m = a ^ (n - m). Тогда получаем:(16 * x) ^ (3/4) × (1/8 * x^ (3/8)) ^ (- 2/3) = (2 ^ 4 * x) ^ (3/4) × (1/2 ^ 3 * x^ (3/8)) ^ (- 2/3) = 2 ^ (4 * 3/4) * x ^ (3/4) * (1/2 ^ 3) ^ (- 2/3) * x ^ (3/8 * (- 2/3)) = 2 ^ 3 * x ^ (3/4) * 1/(1/2 ^ 3) ^ ( 2/3) * x ^ (- 1/4)) = 8 * x ^ (3/4 - 1/4) * (2 ^ 3) ^ ( 2/3) = 8 * x ^ (1/2) * 2 ^ (3 * 2/3) = 8 * x ^ (1/2) * 4 = 32 * x ^ (1/2).